2021
DOI: 10.1039/d1nr00414j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the fractal dimension in self-assembly of terpyridine modified insulin by Fe2+ and Eu3+ to direct in vivo effects

Abstract: Metal ion-induced self-assembly (SA) of proteins into higher-order structures can provide new, dynamic nano-assemblies. Here, the synthesis and characterization of a human insulin (HI) analog modified at LysB29 with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Self-assembled proteins have exhibited wide applications from biomaterials to biomedical engineering due to their inherent properties such as high thermal stability and flexibility, good biocompatibility, and easy of genetic and chemical manipulation . In particular, metal ion-induced self-assembly of proteins can provide new dynamic nanoassemblies with unique structural and functional properties without depending on the extensive experimental work. , Previous reports demonstrated that metal ion, such as Cu 2+ , Zn 2+ , Ni 2+ , Co 2+ , and Fe 2+ , could promote the formation of amyloids by triggering the nucleation and stabilize the amyloids through preventing further growth. , Recently, Yang et al revealed a strategy using Sn 2+ to trigger fast amyloid-like protein assembly into 2D hybrid nanofilms flattening at the air/water interface by reducing the disulfide bonds in hen egg lysozyme . This novel design strategy represents a convenient way to obtain a self-assembled protein interface by dynamic curvature control and site-selective functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled proteins have exhibited wide applications from biomaterials to biomedical engineering due to their inherent properties such as high thermal stability and flexibility, good biocompatibility, and easy of genetic and chemical manipulation . In particular, metal ion-induced self-assembly of proteins can provide new dynamic nanoassemblies with unique structural and functional properties without depending on the extensive experimental work. , Previous reports demonstrated that metal ion, such as Cu 2+ , Zn 2+ , Ni 2+ , Co 2+ , and Fe 2+ , could promote the formation of amyloids by triggering the nucleation and stabilize the amyloids through preventing further growth. , Recently, Yang et al revealed a strategy using Sn 2+ to trigger fast amyloid-like protein assembly into 2D hybrid nanofilms flattening at the air/water interface by reducing the disulfide bonds in hen egg lysozyme . This novel design strategy represents a convenient way to obtain a self-assembled protein interface by dynamic curvature control and site-selective functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-ion-directed reversible self-assembly of peptides and proteins offers the prospect of controlled formation and dissolution of nanoassemblies. We have previously demonstrated that high-order assemblies can be achieved through abiotic ligand–metal-ion interactions using bipyridyl and terpyridyl coordination with Fe 2+ , Cu 2+ , and Eu 3+ for HI and the peptide hormone PYY 3–36 . Their quaternary structure was carefully analyzed by biophysical methods and showed remarkable changes. However, non-natural covalently anchored chelators may raise concerns regarding potential toxicology if the chelator could bind other essential metal ions. , …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we designed and synthesized a dual-ligand as well as a lanthanide-based near-infrared luminescent metal–organic framework (denoted by Eu-MOF/BDC-TPY) for the ratiometric detection of Zn 2+ , using a one-step hydrothermal method (Scheme ). First, we used the ligand 2,2′:6′,2″-terpyridine (TPY), which has been extensively used as a tridentate motif owing to its excellent complexing ability with different metal ions (i.e., main group, transition metals, and lanthanide cations) and was used as a fluorescent indicator that specifically recognizes Zn 2+ . When Zn 2+ was added to the system, a new fluorescence peak appeared at 686 nm and the intensity of this signal gradually increased with the increase in Zn 2+ concentration.…”
mentioning
confidence: 99%